(Mesenchymal) Stem Cell-Based Therapy in Cisplatin-Induced Acute Kidney Injury Animal Model: Risk of Immunogenicity and Tumorigenicity - Ž. Večerić-Haler; A. Cerar; M. Perše (Stem Cells International)
Pathogenesis of AKI is complex and involves both local events in the kidney as well as systemic effects in the body that are interconnected and interdependent. Despite intensive investigations there is still no pharmacological agent that could provide complete protection against cisplatin nephrotoxicity. In the last decade mesenchymal stem cells (MSCs) have been proposed as a potentially useful therapeutic strategy in various diseases, including acute kidney injury. Although MSCs have potent immunosuppressive properties, animal studies also suggest that transplanted MSCs may elicit immune response. Interestingly, tumorigenicity of transplanted MSCs in animal studies has been rarely studied. Since the risk of tumorigenicity of particular therapy as well as the immune response to solid or cell grafts is a major issue in clinical trials, the aim of the present paper is to critically summarize the results of MSC transplantation on animal models of AKI, particularly cisplatin-induced animal models, and to expose results and main concerns about immunogenicity and tumorigenicity of transplanted MSCs, two important issues that need to be addressed in future studies.